Rediscovering empathy : agency, folk psychology, and the human sciences - Stueber, Karsten R. (MIT Press, 2006)
Empathy as epistemically central for our folk psychological understanding of other minds; a rehabilitation of the empathy thesis in light of contemporary philosophy of mind.